Assessment of Environmental Effect of Abandoned Uranium Mine Site in Mika Village of Taraba State Nigeria - E. D, Oruonye; M.Y, Ahmed (International Journal of Geography and Geology, 2017)
Uranium ore has been mine for decades before it was abandoned in Mika village of Yorro LGA of Taraba state. Uranium mining poses high risk of radiation exposure to members of the public and local community. Despite the high risk associated with uranium ore deposit and mining in the area, the local community have continued to live in the surroundings of the abandoned mine sites and engaging in their day to day socio-economic activities. No attempt has been made to investigate the characteristics and current condition of the abandoned uranium mine site in the area and its potential impacts on the socio-economic life of the people. This study examined the potential environmental impact that could arise from the abandoned uranium mine site and associated past activities. Data was generated through desk review of existing data sources, including literatures, field observation and measurements of abandoned uranium mine pits and related features. Measuring tape and Garmin 12 X GPS (Global Positioning System) was used in the measurements. Interview of key informants was also carried out. Findings from the study show that the uranium ore is found on hill top (425metre above sea level). The mine wastes and overburden were deposited around the mine pits. Most of the overburden materials have been washed away. Findings from the study revealed that scooping of uranium ore samples have been ongoing in Mika area before independence in 1960. The uranium mineral samples collected from the site were taking to France and subsequently to Iran. Despite the risk posed by the abandoned uranium mine pit, the local communities insist that they did not observe any strange sickness or effects associated with the mining activities. Many of them depend on the water collected in the abandoned uranium mine pit for domestic consumption. Based on the findings, the study recommends periodic monitoring of water and agricultural crop to ascertain the possible effects of radioactivity associated with the uranium ore deposits in the area and enlightenment of the local communities on the potential impact of the abandoned uranium mines on their land, soil, air and water in the area.